Verificação oportunista de assinaturas digitais para programas e bibliotecas em sistemas operacionais paginados - Destefani, Guilherme Herrmann (2005)
This work discusses a series of security mechanisms based in cryptography, combining them with concepts of operating systems, in order to create an innovative architecture that uses some functionalities characteristics of operating system to protect it against vulnerabilities related with the adulteration of computer programs and libraries. This architecture consists in a mechanism for generation of digital signatures integrated into the computer programs and libraries, in order to guarantee the software and operating system authenticity and integrity while in execution by the target machine. The system is transparent to programmers, and it is also possible that software with digital signatures can be executed on systems without support to verification of signature, what simplifies the software distribution process. The verification of signatures is integrated with the paging mechanism of the microprocessor, making on-demand verification only in the part of the programs and libraries that is going to be effectively used, diminishing the impact on the performance and providing transparency for final users and system administrators. The validation of the model was carried through as an extension to the application binary interface Unix ELF, implemented in the GNU/Linux platform. The impact of the digital signature for developers and distributors of operating systems under the point of view of complexity, effect for final users and overload in performance of the system was verified. xix